Dampak Pembelajaran Kewirausahaan, Media Sosial Terhadap Minat Berwirausaha Siswa SMK Trunojoyo Jember - Shendy Andrie Wijaya; Neviyani Neviyani; Ervin Nurah Masari (Perspektif Pendidikan dan Keguruan, 2022)
This research is motivated by the existence of entrepreneurship learning and social media conducted by the school. With this, it shows an increase in students` interest in entrepreneurship so that it can be formulated in this study that how is the impact of entrepeneurship learning and social media both partially and simultaneously on interest in entrepreneurship. This study aims to analyze and determine the impact of entrepreneurship learning and social media on interest in entrepreneurship. From primary data obtained through questionnaires distributed to class XII students at Trunojoyo High School, Jember. The population in this study were students of class XII BDP 1, 2 and 3, amounting to 75 respondents. And in this study the sample used amounted to 75 respondents of class XII BDP students. The type in this research is quantitative using multiple linear regression analysis method with data processing using SPSS IBM version 25. The hypothesis test in this study is the t test and f test with a value level of = 5%. From the results of the t-test research, the first variable of entrepreneurial learning on interest in entrepreneurship has a value of 10.610>1.6660 with a significance of 0.000 so that there is a partially significant effect. The t-test data analysis of the second variable of social media on the interest in entrepreneurship has a value of 151.826> 1.6660 with a significance of 0.000 so that there is a significant effect. Furthermore, the analysis of the f test data Simultaneously the independent variables (entrepreneurship learning and social media) in this study had a value of 20478 > 3.12 so that there was a significant influence on the dependent variable, namely the interest in entrepreneurship in class XII BDP students at at Trunojoyo High School, Jember